Role-Playing Method to Improve Mathematics Learning Outcomes for Mildly Intellectually Disabled Students - Radhiyya, Hana Rabby; Erlani, Lalan; Jaya, Indra (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2025)
This classroom action research aims to improve mathematics learning outcomes on the topic of currency fractions of 500, 1000, and 2000 for eighth grade students with mild intellectual disabilities by applying the role-playing method. The sample in this study consisted of 5 students with mild intellectual disabilities from Class VIII at SLB BC Nurasih Bintaro. The research employed a classroom action research method using the Kemmis and McTaggart model. Data were collected through tests, which were analyzed quantitatively, and non-test techniques (observation, interviews, and documentation), which were analyzed qualitatively. The results showed that the average mathematics learning outcome on the initial ability test was 64. In Cycle I, the students’ average score increased by 14 percent to 78. In Cycle II, the average score rose again to 85. These results indicate that the role-playing method can be considered an effective effort to improve mathematics learning outcomes on the topic of currency fractions for students with mild intellectual disabilities.